Generation of Intense Single-Cycle Pulse in the Air Based on All Solid-State System - Seo, Meenkyo; Tsendsuren, Khurelbaatar; Mitra, Sambit; Kling, Matthias Friedrich; Kim, Dongeon (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We use thin solid plates in a double stage multi-plate configuration to produce high-contrast, intense single-cycle pulse at 3 kHz. Generated spectrum spans from 400 to 1000 nm at-20 dB intensity level. Output pulses are compressed down to 2.6 fs (transform-limit 2.55 fs) with an energy of 0.235 mJ.
CRIS-Team Scopus Importer:2023-04-20